Navigating Pregnancy: Information Sources and Lifestyle Behavior Choices—A Narrative Review - Christina Gjestvang; Lene Annette Hagen Haakstad (Journal of Pregnancy)
Conclusions: Pregnant individuals relied on the Internet and HCP, with a preference for the Internet despite trust in midwives. Several sources of health information were positively associated with adherence to GWG and nutrition recommendations. Improving the quality of online information should be a priority for policymakers and health authorities.